Kompetensi Guru BK SMA Negeri 10 Medan dalam Memahami Kode Etik Profesionalisme Seorang Guru Bimbingan dan Konseling - Rina Suryani; Ebi Alonta Br Tarigan; Hestu Ayudia Pangesty; Khairumi Asra Putri; Widia Aprianjelicha Tarigan (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This study aims to determine the competence of counseling teachers at SMA Negeri 10 Medan in understanding the professional code of ethics of a guidance and counseling teacher. The method used is a qualitative descriptive approach. Informants in this study include counseling teachers. the subjects in this study were BK teachers, amounting to 2 people. The data collection technique that the researchers used in this study was an interview technique. Processing techniques and data analysis is done by way of qualitative descriptive analysis. The results of the study show the competence of BK SMA Negeri 10 Medan in Understanding the Code of Professional Ethics of a Guidance and Counseling Teacher. The results of this study indicate that overall competency in Understanding the Code of Ethics of guidance and counseling teachers in the implementation of guidance and counseling services at SMA Negeri 10 Medan has been able to applied, the counseling teacher also understands what the substance of guidance and counseling is. Counseling teachers at SMA Negeri 10 Medan have also tried to carry out their duties and roles as a counseling teacher, and provide the best service to solve problems experienced by students. Counseling teachers at SMA Negeri 10 Medan have also been able to apply counseling services and models, although some of them are still learning and some say they are not optimal. Keywords: Counseling Teacher Competency, Code of Ethics, Professionalism